Attractive FDI : How Much Does Investment Climate Matter? - Hornberger, Kusi; Battat, Joseph; Kusek, Peter (World Bank, Washington, DC, 2012)
Business opportunities-as reflected in the size and growth potential of markets-are the most powerful drivers of foreign direct investment. But investment climate features such as strong institutions and investor friendly regulations also matter and may even boost the development impact of the investment. Moreover, many elements of the investment climate can be reformed in the short run and at comparatively low cost. Improving the investment climate therefore offers an excellent opportunity for countries seeking to attract foreign direct investment.